2020
DOI: 10.3389/fphys.2020.00899
|View full text |Cite|
|
Sign up to set email alerts
|

circAFF1 Aggravates Vascular Endothelial Cell Dysfunction Mediated by miR-516b/SAV1/YAP1 Axis

Abstract: Pathological vascular endothelial damage caused by hypoxia is the basis of many vascular-related diseases. However, the role of circular RNA in hypoxic vascular injury is still poorly understood. Here, we found that hypoxia induced AFF1 circular RNA (circAFF1) can activate the SAV1/YAP1 and lead to the dysfunction of vascular endothelial cells. In HUV-EC-C and HBEC-5i cells, circAFF1 was upregulated under CoCl 2 induced hypoxic conditions. The abnormal expression of circAFF1 inhibited the proliferation, tube f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, early events after SAH cause EC dysfunction and cell apoptosis, which in turn exacerbates the delayed phase of SAH pathophysiology [ 34 ]. Wang et al, demonstrated that circAFF1 was upregulated in ECs that under hypoxic conditions by cobalt chloride (CoCl2) and causes ECs to malfunction [ 35 ]. Was demonstrated that upregulation of circAFF1 can suppress the proliferation and tube formation and promote the apoptosis of ECs in vitro.…”
Section: Potential Circrnas In Iamentioning
confidence: 99%
“…However, early events after SAH cause EC dysfunction and cell apoptosis, which in turn exacerbates the delayed phase of SAH pathophysiology [ 34 ]. Wang et al, demonstrated that circAFF1 was upregulated in ECs that under hypoxic conditions by cobalt chloride (CoCl2) and causes ECs to malfunction [ 35 ]. Was demonstrated that upregulation of circAFF1 can suppress the proliferation and tube formation and promote the apoptosis of ECs in vitro.…”
Section: Potential Circrnas In Iamentioning
confidence: 99%
“…Recently, the functions of AFF1 in the neural system were investigated. It has been demonstrated that the expression of circAFF1 was upregulated in patients with SAH and overexpression of circAFF1 inhibited the proliferation, tube formation, migration and contributed to apoptosis of endothelial cells ( Wang et al, 2020a ).…”
Section: Circular Rnas Expressed In Acute Central Nervous System Inju...mentioning
confidence: 99%
“…Recent evidence suggests that the hypoxia-induced circAFF1 can lead to disordered vascular ECs through triggering SAV1/YAP1. From the mechanical perspective, the circAFF1/miR-516b/SAV1/YAP1 axis partially contributes to vascular endothelium dysfunction, and it may be used as an indicator of hypoxia injury-induced vascular diseases [ 108 ]. Furthermore, significantly upregulated cZNF609 was observed by Liu et al in HUVECs exposed to hypoxia and HG environments.…”
Section: Potential Circrnas In Aaasmentioning
confidence: 99%